Trauma Anesthesia - Smith, Charles E.; Como, John J. (Cambridge medicine (Series), 2015)
Trauma patients present a unique challenge to anesthesiologists, since they require resource-intensive care, often complicated by pre-existing medical conditions. This fully revised new edition focuses on a broad spectrum of traumatic injuries and the procedures anesthesiologists perform to care for trauma patients perioperatively, surgically, and post-operatively. Special emphasis is given to assessment and treatment of co-existing disease, including surgical management of trauma patients with head, spine, orthopedic, cardiac, and burn injuries. Topics such as training for trauma (including use of simulation) and hypothermia in trauma are also covered. Six brand new chapters address pre-hospital and ED trauma management, imaging in trauma, surgical issues in head trauma and in abdominal trauma, anesthesia for oral and maxillofacial trauma, and prevention of injuries. The text is enhanced with numerous tables and 300 illustrations showcasing techniques of airway management, shock resuscitation, echocardiography and use of ultrasound for the performance of regional anesthesia in trauma